Marriage and employment participation with wage bargaining in search equilibrium. (2nd August 2021) - Bonilla, Roberto; Trejos, Alberto
Abstract: We build an equilibrium search model where married couples make joint decisions on home production and labour market participation and analyse the implications of our results for a frictional marriage market. A worker's bargaining position reflects their productivity, and the productivity and employment status of their spouse. People sometimes accept transitory jobs only to raise the spouse's long‐term wages. Firms sometimes reduce turnover by unilaterally increasing a worker's wage, ensuring that the spouse stays at home.